Analyzing the effect of building permit issuance on the housing delivery system in Ghana - Hammah, Noriss Kweku; Ibrahim, Rahinah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2014)
A building permit serves as a green light in housing development schemes. Hence, without the requisite consent from the relevant local authorities, no housing development can legally take place. In Ghana, it is widely known that the waiting period for permit approval is too long as it routinely takes years to get a building permit. As a result, the housing delivery system is badly affected and thus it causes an ongoing increase in housing deficits on an annual basis. Ghana requires an additional 140,000 housing units annually and current supply is only about 45,000 units per annum. This paper posits that prolonged delays in the permit process are one of the main factors leading to housing deficits in Ghana. While planning workflow could be streamlined, the paper theorizes on how organizational structure could influence the performance of the property development’s workflow. The objective of this paper is to identify potential areas for improvements in the current Ghanaian building approval process. It concludes with recommendations towards improving organizational and permit process as it relates to the various building authorities in Ghana.